Access to primary care for socioeconomically disadvantaged older people in rural areas: a realist review. Issue 5 (17th May 2016) - Ford, John A; Wong, Geoff; Jones, Andy P; Steel, Nick
Abstract : Objective: The aim of this review is to identify and understand the contexts that effect access to high-quality primary care for socioeconomically disadvantaged older people in rural areas. Design: A realist review. Data sources: MEDLINE and EMBASE electronic databases and grey literature (from inception to December 2014). Eligibility criteria for selecting studies: Broad inclusion criteria were used to allow articles which were not specific, but might be relevant to the population of interest to be considered. Studies meeting the inclusion criteria were assessed for rigour and relevance and coded for concepts relating to context, mechanism or outcome. Analysis: An overarching patient pathway was generated and used as the basis to explore contexts, causal mechanisms and outcomes. Results: 162 articles were included. Most were from the USA or the UK, cross-sectional in design and presented subgroup data by age, rurality or deprivation. From these studies, a patient pathway was generated which included 7 steps (problem identified, decision to seek help, actively seek help, obtain appointment, get to appointment, primary care interaction and outcome). Important contexts were stoicism, education status, expectations of ageing, financial resources, understanding the healthcare system, access to suitable transport, capacity within practice, the booking system and experience of healthcare. Prominent causal mechanisms were health literacy, perceived convenience, patient empowerment and responsiveness of the practice. Conclusions: Socioeconomically disadvantaged older people in rural areas face personal, community and healthcare barriers that limit their access to primary care. Initiatives should be targeted at local contextual factors to help individuals recognise problems, feel welcome, navigate the healthcare system, book appointments easily, access appropriate transport and have sufficient time with professional staff to improve their experience of healthcare; all of which will require dedicated primary care resources.